analisa - Raven Zayyan Tsaqif Raven; Sulaiman Ali; Mahmudin Marbun (Jurnal Inotera, 2024)
PT Agro Sinergi Nusantara (ASN), one of the industries engaged in the Palm Oil Mill (PKS) industry, is located in Teunom, Aceh Jaya Regency. The Ripple Mill machine is one of the important machines used in Palm Head Mills which functions as a separator or splitter of kernel kernels and palm shells by utilizing centrifugal force to produce Palm Kernel Oil. From the initial analysis, it is known that the use of Ripple Mill machines in the industry today often experiences donwtime or damage. The purpose of this study is to analyze the damage of the Ripple Mill machine at PT ASN's Palm Oil Mill using the Failure Mode and Effects Analysis (FMEA) method and Fishbone diagram. The results of the study obtained damage to the Ripple Mill machine in the identification of 5 (five) malfunctions or failure modes that occurred. using the FMEA method, it is known that the most dominant Ripple Mill machine failure mode occurs is the fracture of rotor bar components due to the entry of hard objects with the Risk Priority Number (RPN) which is 384 and using the fishbone diagram method, it is known that there are (four) influencing factors, namely human, machine, environmental and method factors.